The Craft Of Teaching Arabic (Phonology,Vocabulary,Syntax) - Djoukhrab, Souad (Journal of Ecohumanism, 2025)
Applied linguistics is a subfield of linguistics that emerged in 1946, at a time when interest in the challenges of teaching living languages to foreigners was growing, alongside the flourishing of applied studies. Applied linguistics is closely linked to language teaching, particularly to structural and descriptive linguistics, which have significantly influenced language teaching methods and exercises. These exercises are considered the most important and effective tools in linguistic education. This paper aims to explore the nature, function, and role of language exercises in the language acquisition process. We will also examine structural exercises, their pedagogical approaches, types, and procedural applications, as well as the critiques directed at them. Furthermore, we will discuss communicative exercises and their effectiveness in mastering sentence structures and constructing grammatically correct sentences. The goal of this research is to provide a clear overview of the scientific standards used in designing language exercises, their linguistic content, and the tasks involved. It will also present an understanding of the characteristics, functions, and placement of exercises within a lesson plan.